Images of an Australian enlightenment: the story of Lachlan and Elizabeth Macquarie's treatment of the convicts as a history tale for today - Lovegrove, Austin (Unicorn, 2019)
This is the story of two Scots, Lachlan Macquarie, governor of the British colony of New South Wales from 1810 to 1821, and of his wife, Elizabeth Macquarie, both of whom pioneered a policy of rehabilitation and renewal as part of their treatment of the convicts. 0The first part of the book canvasses what the Macquaries set out to achieve, and their stated reasons for this, as well as enquiring into the deeper personal forces at work within their lives. It introduces their supporters and opponents both in the Colony and in Britain. 0In the second part, the idea of enlightenment is introduced, its definition based on Churchill's understanding of what it means for a society to be civilized. In this light, the punitive thinking of the Macquaries' opponents both in Britain and the Colony represent darkness. In contrast, the Macquaries' work is seen as an enlightenment, one having the potential to inform, indeed challenge, the darkness of the current punitive climate of public opinion so characteristic of much of the Western world today. 0Following this, comes an overview of a proposal for a very different approach to the treatment of crime and criminals. There are barriers to this - ones identified by studying what a number of the enlightened minds in Britain at the time of the Macquaries were saying. Yet, there are today pockets of enlightenment to be discerned. Accordingly, though the Macquarie governorship ended in personal tragedy for the two of them, there is the opportunity for a second Age of the Macquaries, one not just confined to a remote, tiny corner of this world. --